GEO-SOCIAL TAGGING AS A CREATIVE WAY TO COMMUNICATE STORIES ON GEOGRAPHIES - Elisa Bonacini (CCIT Journal, 2013)
The aim of this paper is to show how the evolution of ICTs in the field of digital cultural participation has helped turn geo-social tagging into a new form of creation of cultural value through user-generated contents (UGC). In order to demonstrate the potential of these digital tools, we will base our study on some examples of geotagging and geo-social blogs, in Italy and abroad. Tagging a place is giving that place a story: this means being able to write digital stories on geographies. Tagging a place enables us to rediscover our territory in a new and shared way, creating forms of real social tagging and urban digital storytelling